2020
DOI: 10.1093/gji/ggaa610
|View full text |Cite
|
Sign up to set email alerts
|

Apparent earthquake rupture predictability

Abstract: Summary To what extent can the future evolution of an ongoing earthquake rupture be predicted? This question of fundamental scientific and practical importance has recently been addressed by studies of teleseismic source time functions (STFs) but reaching contrasting conclusions. One study concludes that the initial portion of STFs is the same regardless of magnitude. Another study concludes that the rate at which earthquakes grow increases systematically and strongly with final event magnitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…As our STF model has access to the acceleration parameter investigated in this study, we would expect to be able to reproduce this effect. However, later analysis demonstrated that these results were caused by a sampling bias, which our study confirms (Meier et al, 2020). Danré et al (2019) analysed STFs as well, in this case by decomposing them into subevents, and also found predictability.…”
Section: Comparison With Previous Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…As our STF model has access to the acceleration parameter investigated in this study, we would expect to be able to reproduce this effect. However, later analysis demonstrated that these results were caused by a sampling bias, which our study confirms (Meier et al, 2020). Danré et al (2019) analysed STFs as well, in this case by decomposing them into subevents, and also found predictability.…”
Section: Comparison With Previous Resultssupporting
confidence: 74%
“…This introduces a systematic bias in the first seconds Vallée & Douet (2016). This bias has also been analyzed quantitatively in prior publications Meier et al (2020).…”
Section: A Apparent Early Predictability In Scardecmentioning
confidence: 79%
“…This would lead to magnitude underestimation because of the magnitudes calculated from the newly triggered stations (Melgar and Hayes, 2019;Trugman et al, 2019;Chung et al, 2020) using a short P-wave time window (less than 2 s), especially for the MEMS-based stations ∼50 km away from the epicenter (Table 3). Usually, for a large earthquake with rupture duration longer than 4 s, the magnitude calculated from such a short window will be significantly underestimated (Meier et al, 2016(Meier et al, , 2021Trugman et al, 2019). To avoid this risk, we can use the time window length of each triggered station as a weight for computing the network magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Then the temporal evolution of the observed and predicted intensity envelope updates as the FinDer magnitude and orientation of line source changes. When applying the lower alert threshold and higher damage threshold, a potential expected consequence is to yield better classification as suggested by previous tentative and observational studies Ruhl et al 2019;Meier et al 2020;Chung et al 2020). To evaluate the influence of alert criterion exerting on the classification performance during the Ridgecrest earthquake sequence, we provide six choices of alert criterion to explore in which circumstance FinDer algorithm can achieve the best alert performance including classification.…”
Section: The Simulated Real Time Alert Performancementioning
confidence: 99%